A White Country? The Intricacies of Race in Argentina (KULT_online, 2017)
Rethinking Race in Modern Argentina is a thought-provoking volume discussing the evolution of the conceptualization of race in Argentine history and culture. The book questions the presumed homogenous whiteness of Argentina and presents how race became invisible in Argentine discourses and how diverse actors attempt to find new ways to debate the racial intricacies of the country. The volume suggests that in Argentina the category of whiteness was both in a certain sense inclusionary, but also a discriminatory, exclusionary, hierarchical structure.